South Georgia, South Sandwich and South Orkney Islands / Publication of the Office of the Chief of Hydographic Service of the Navy (USSR) - Soviet Union. Военно-Морской Флот; Soviet Union. Гидрографическое управление. Военно-Морских Сил; Soviet Union. Voenno-Morskoĭ Flot; Soviet Union. Gidrograficheskoe upravlenie. Voenno-Morskikh Sil (Washington, DC : U.S. Navy Hydrographic Office, 1959)
1st edition August 30, 1949. Reproduced by the U.S. Navy Hydrographic Office (November 1959) from U.S.S.R. Chart Relief shown by form lines. Depths shown by soundings and isolines.; "U.S.S.R. 146" -- Top and bottom margin.; Map in Russian and English.; Non-Latin script record Grayscale; 1:3,500,000